2022
DOI: 10.12968/bjon.2022.31.8.s14
|View full text |Cite
|
Sign up to set email alerts
|

Complications of peripheral intravenous catheters and risk factors for infiltration and phlebitis in children

Abstract: Aim: This study aimed to identify the types of complications of peripheral intravenous catheters (PIVCs) in hospitalised children and possible risk factors for the development of extravasation, infiltration and phlebitis. Method: The study was conducted in the largest children's hospital in a region of Turkey, with a bed capacity of 354 and 1400 employees, which provides care only to paediatric patients aged from newborn to 18 years old. In this 5-month prospective study, the complications of PIVCs in hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…In a recent article from the authors' centre focusing on central line bundles in different clinical settings, single-use prefilled flushing 0.9% sodium chloride syringes were found to be an important step in the central line bundle, and these bundles should be adapted to include PIVCs (Karaoğlan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent article from the authors' centre focusing on central line bundles in different clinical settings, single-use prefilled flushing 0.9% sodium chloride syringes were found to be an important step in the central line bundle, and these bundles should be adapted to include PIVCs (Karaoğlan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40] In addition, the delicate and complex nature of neonatal ward work, coupled with environmental factors such as instrument alarms and infant crying, can significantly impact nurses' emotional stability and psychological qualities, potentially affecting the success rate of punctures leading to neonatal extravasation. 41,42…”
Section: Nurse Factors and Extravasation Of Intravenous Fluids In Neo...mentioning
confidence: 99%
“…There was no statistically significant association between grads of PIVC complication and children's age and site of PIVC insertion. In contrast, another stated that age, hospitalization in surgery unit, insertion in antecubital vein have role in development of phlebitis study [20]. Results from another study revealed that younger ages are risk factors for PIVC complications in children [21].…”
mentioning
confidence: 97%